Securing America's passenger-rail systems - Wilson, Jeremy M., 1974- (RAND Corp., 2007)
U.S. communities depend on reliable, safe, and secure rail systems. Each weekday, more than 12 million passengers take to U.S. railways. This book explains a framework for security planners and policymakers to guide cost-effective rail-security planning, specifically for the risk of terrorism. Risk is a function of threat, vulnerability, and consequences. This book focuses on addressing vulnerabilities and limiting consequences.